(untitled) (Al-Qamar, 2021)
After the passing away of the Blessed One, the consensus of the Companions was established. Just as according to all the jurists, Ijmaa is the evidence in the Shari’ah and is the main source of the Shari’a, in the same way, they all agree on the consensus of the Companions of the Prophet, may Allah bless them and grant them peace, and all the jurists declare that it is necessary to act on it. If there are many sayings of the Prophets, then the one that is closest to the Shariat should be adopted; But the followers and followers were not bound by this principle in the sayings of the followers. The Companions of the Prophet, may God bless them and grant him peace, were the first to realize this need; So, for this purpose, during the caliphate of Hazrat Omar, the great Companions of the Prophet, may God bless him and grant him peace, were prevented from going out; So that they can be taken advantage of to solve the problems that have arisen and what they all agree on is considered as the consensus of the Ummah.